A New Development in Front Group Strategy: The Social Aspects Public Relations Organization (SAPRO) - Pietracatella, Rachel; Brady, Danielle (Frontiers in Communication, 2020)
Increased pressure on risk industries to reduce their negative impact on society has resulted in an increasing volume of ‘risk’ and ‘responsibility’ communications from interest groups known as Social Aspects Public Relations Organisations (SAPROs). SAPROs have been criticised for being the ‘front groups’ of risk industries (e.g., the tobacco, gambling, sugar and alcohol industries). Operating within the neoliberal policy framework, SAPROs seek to forestall regulation and prioritise industry profits over public health. Building on risk industry research from the public health sphere, this article examines the SAPRO phenomenon and situates it in the political public relations (PR) literature. Specifically, it considers how SAPROs perform an indirect lobbying function on behalf of their funding industries. Using DrinkWise as an example of an alcohol SAPRO, this article shows that SAPROs represent a novel development in front group strategy and examines how this development intersects with neoliberalism. This article also argues that SAPROs are deployed by risk industries to hegemonically promote the idea of personal responsibility and that their indirect lobbying function may be necessary to the continuance of neoliberal policies.